The Impact of Streamer Characteristics and Content Quality on Consumer Purchase Intention: Evidence from Indonesia’s TikTok Shop - Rahajeng Tyas Astari; Soepriyatna (Journal of Business, Management, and Social Studies, 2026)
This study investigates the influence of streamer characteristics and content quality on consumer purchase intention within Indonesia’s rapidly growing TikTok Shop live-streaming environment. Grounded in the Elaboration Likelihood Model (ELM), the research addresses existing contradictions in social commerce literature by assessing how dual information-processing routes shape consumer decisions. A quantitative, explanatory research design was deployed using an online survey. Data were collected from a sample of 63 Indonesian consumers who had watched or transacted on TikTok Live within the preceding six months. Structural relationships were analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS software. The structural model examined the central route (Argument Quality), the peripheral route (Streamers’ Credibility and Source Attractiveness), and the interactive environment (Interactivity) against the endogenous variable (Purchase Intention). The PLS-SEM analysis revealed that the model explained 44.9% of the variance in Purchase Intention. Three of the four hypothesized paths were statistically supported. Argument Quality emerged as the strongest positive driver, followed closely by Streamers’ Credibility and Interactivity. Conversely, Source Attractiveness did not exert a statistically significant influence on purchase intention. Applying the Elaboration Likelihood Model to Indonesia's TikTok Shop live-streaming context reveals that purchase intentions are driven primary by substantive product information (central route) alongside streamer credibility and real-time interactivity, whereas visual appearance cues like source attractiveness hold no statistically significant influence.